"We don't want to run before we walk": the attitudes of Australian stakeholders towards using psychedelics for mental health conditions - Breanne E Kunstler; Liam Smith; Christopher J Langmead; Denise M Goodwin; Breanna Wright; Melissa A Hatty (Sax Institute, 2023)
Objectives: This study was aimed at understanding the attitudes and positions of key Australian organisational and political stakeholders towards using psychedelic agents in medically supervised environments to treat mental health conditions. Specifically, this research was designed to identify some of the issues that might impede the clinical implementation of psychedelics. Methods: Semi-structured interviews were conducted with four Australian politicians and nine representatives of key stakeholder organisations between September 2022 and January 2023. Data analyses were completed using pattern-based inductive thematic analysis. Results: Participants were cautiously optimistic about using psychedelics to treat mental health conditions, with hesitancy emerging due to the perceived inadequacy of research into the efficacy and feasibility of these treatments. Politicians consistently mentioned that negative stigma prevented them and their peers from supporting the use of psychedelics in Australia. Effective, evidence-based, clear messaging that refutes misconceptions, uses persuasive messaging and provides clear information to inform implementation is needed to improve knowledge and challenge attitudes, biases and emotions that can influence the debate around psychedelics. Conclusions: Stakeholder representatives and politicians agree that insufficient evidence exists to support the widespread clinical implementation of psychedelics in Australia. Politicians also perceive the stigma associated with psychedelics might negatively influence progressive legislation. Additional research and a clear presentation of this research are needed before the clinical use of psychedelics can be supported.